A Cross-Sectional Study of Staff Nurses’ Awareness and Practices about Standard Precautions in a Tertiary Care Hospital in South Karnataka - Trupti B. Naik; L. Bhageerathi (Issues and Development in Health Research Vol. 4, 2021)
Background: Infections obtained at a hospital or other healthcare facility in which the illness was not present or incubating at the time of admission are known as hospital-acquired infections (HAIs). Illnesses acquired at the hospital but showing up after discharge, as well as infections among the facility’s health care employees, are included. Nurses are major contributors to care in all health care settings, and their knowledge and behaviors are critical in the control and prevention of HAIs. Objective: The goal of this study was to determine the level of awareness and practice of standard precautions among the staff nurses. Materials and Methods: The present study was a hospital-based descriptive study that took place from January to March 2017 at Chamarajanagar Institute of Medical Sciences at Chamarajanagar. A total of 40 staff nurses were chosen using simple random sampling, and data was collected using a pretested and semi-structured questionnaire. Microsoft Office Excel 2007 was used to conduct the statistical analysis. Results: The majority, 35 (87.5%), knew about the Infection Control Committee (ICC) and the Central Supply and Sterilization Department (CSSD), and > 90% knew about segregation and disposal according to BMW guidelines. The majority of staff nurses, 38 (95%), cleaned their hands before and after touching patients and donned personal protective equipment. More than half i.e. 23 (57.5%) of the participants in the study had experienced a needle stick injury, yet only 19 (47.5%) of them reported it and sought treatment. 24 (60%) of the staff nurses received a hepatitis B immunization. Conclusion: The current study reveals that the staff nurses have a sufficient degree of knowledge and practices regarding standard precautions, and also identifies several places where educational interventions are required.